Refugee economies in Uganda: What difference does the self-reliance model make? - Betts, A; Chaara, I; Omata, N; Sterck, O (Refugee Studies Centre, 2019)
Uganda’s refugee policies have been widely recognised as among the most progressive in the world. Through its self-reliance model, it allows refugees the right to work and freedom of movement. It has sustained this approach virtually since independence despite currently hosting more refugees than any other African country. Uganda’s model has three core elements that distinguish it from most other refugee-hosting countries. First, its regulatory framework: it lets refugees work and choose their place of residence. Second, its assistance model: it allocates plots of land for refugees to cultivate within its rural settlements. Third, its model of refugee–host interaction: it encourages integrated social service provision and market access. This report explores the question: what difference does Uganda’s self-reliance model make? How do its different elements influence welfare outcomes for refugees and for host communities? These questions matter both for Uganda and for refugees around the world. Given that Uganda’s model has become an exemplar for development-based approaches to refugees, an evidence-based understanding of the conditions under which self-reliance policies lead to enhanced welfare outcomes matters for policy, programming, and advocacy.